Classification and biological identity of complex nano shapes - Luca Boselli (Nature Portfolio, 2020)
Nanostructures are observed in many areas of materials science, and are often loosely described based on their shape. Here, a framework is presented for the categorization of nanoparticles based on their statistically defined geometry.